Stable and variable affordances are both automatic and flexible - Borghi, Anna M.; Riggio, Lucia (Frontiers in Human Neuroscience, 2015)
The mere observation of pictures or words referring to manipulable objects is sufficient to evoke their affordances since objects and their nouns elicit components of appropriate motor programs associated with object interaction. While nobody doubts that objects actually evoke motor information, the degree of automaticity of this activation has been recently disputed. Recent evidence has indeed revealed that affordances activation is flexibly modulated by the task and by the physical and social context. It is therefore crucial to understand whether these results challenge previous evidence showing that motor information is activated independently from the task. The context and the task can indeed act as an early or late filter. We will review recent data consistent with the notion that objects automatically elicit multiple affordances and that top-down processes select among them probably inhibiting motor information that is not consistent with behaviour goals. We will therefore argue that automaticity and flexibility of affordances are not in conflict. We will also discuss how language can incorporate affordances showing similarities, but also differences, between the motor information elicited by vision and language. Finally we will show how the distinction between stable and variable affordances can accommodate all these effects.